A Prospective Analysis of Neuromonitoring for Confirmation of Lead Placement in Dorsal Root Ganglion Stimulation. Issue 6 (2nd August 2017) - Falowski, Steven M; Dianna, Andreas
Abstract: BACKGROUND: Dorsal root ganglion stimulation is a neuromodulation therapy used for chronic neuropathic pain. Typically, patients are awakened intraoperatively to confirm adequate placement. OBJECTIVE: To determine whether neuromonitoring can confirm placement in an asleep patient. METHODS: This is a prospective analysis of 12 leads placed in 6 patients. Lead confirmation was confirmed by awake intraoperative testing, as well as asleep testing utilizing neuromonitoring. Patients were used as their own control. Sensory and motor thresholds for each patient with awake and asleep neuromonitoring testing were recorded. Intraoperative impedance and postoperative programming were also recorded. RESULTS: In each patient, paresthesias were generated prior to motor contractions in the awake patient. For each patient, somatosensory evoked potential responses were present after lowering below the dropout threshold of electromyogram responses with neuromonitoring. There were varying degrees of separation in the thresholds that did not appear to be consistent across level or diagnosis. Smaller degrees of separation between thresholds during awake testing also held true in the asleep patient. This was further confirmed with postoperative programming. Impedances did not alter the separation in thresholds or amount of stimulation required for responses. One patient was combative during awake testing, and therefore motor thresholds were not obtained. This same patient was determined to have a ventral placement, confirmed with awake and asleep neuromonitoring testing. CONCLUSION: This series demonstrates that the proposed neuromonitoring protocol can be used in an asleep patient to assure proper positioning of the dorsal root ganglion electrode in the dorsal foramen by generating somatosensory evoked potential responses in the absence of electromyogram responses.